昭和病院におけるインフルエンザ発症状況 - 藤原 弘一; 新田 豊美; 橋口 英志; 平野 英保; 坂本 久浩; 吉水 卓見 (The Journal of Showa Hospital, 2007)
Infection status of influenza A or B viruses have to be every summer and winter might be the curios-ity among people.. We analyzed the winter infection status for 4 months (Dec, Jan, Feb, March) during 2004/2005 and 2005/2006 at Showa Hospital. Espline influenza A & B was used to determine types using rhi-norhoe. Type B influenza was founds 3 patients in February, 14 patients in March, that is, total 14 infected from December 2004 to March 2005. Type A influenzas were detected 35 patients on January 10 patients in Febru-ary from December 2005 to March 2006. The peak of the patients infected type A virus appeared 1 month faster than type B. Higher infection rates were detected among the hospital wards, such as the clouded with in and out people, and the many patients wandering around the ward's corridor. These data suggested that work-ing stuffs should receive vaccine injections before the infection disaster occurred. 昨年、今年と夏場のインフルエンザの流行が話題になっている。今回2004年の年末から2005年(2004/2005)と2005年の年末から2006年(2005/2006)にかけての本院入院患者のインフルエンザ発生状況について調べたので報告する。 使用したインフルエンザ迅速診断キットはエスプラインインフルエンザキットA&B。2004/2005年の患者数は2月3名、3月14名の計17名で全てB型。2005/2006年は1月35名、2月10名で計45名、全てA型であった。ピークは前年に比べて1カ月はやかった。 また病棟毎の比較をみると差があり、徘徊患者の多い病棟と人の出入りの多い病棟に多い傾向にあった。なお、昭和病院職員のワクチン接種率は把握出来る範囲では68.2% (2005/2006) であった。この結果を今季のインフルエンザ対策に活かしたいと考えている。